Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1007/s00535-007-2022-3
|View full text |Cite
|
Sign up to set email alerts
|

Validity of endoscopic classification of nonerosive reflux disease

Abstract: Frequency of abnormal acid reflux with NERD is higher in patients with minimal changes than in patients without such changes. Minimal changes are most likely attributable to gastric acid reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 22 publications
4
53
0
Order By: Relevance
“…An investigation of the relationship between RE endoscopic findings and GERD symptoms also demonstrated that about 60% of RE relapsed cases had developed no GERD symptoms at the time of RE relapse. Several reports to date have also indicated that RE endoscopic findings were not accompanied by GERD symptoms (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), and this trend was often found in elderly (28). It has also been reported that the percentage of severe RE is higher in the elderly than in juveniles, whereas the frequency of severe heartburn in patients with severe RE is lower in the elderly (27,36).…”
Section: Discussionmentioning
confidence: 91%
“…An investigation of the relationship between RE endoscopic findings and GERD symptoms also demonstrated that about 60% of RE relapsed cases had developed no GERD symptoms at the time of RE relapse. Several reports to date have also indicated that RE endoscopic findings were not accompanied by GERD symptoms (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), and this trend was often found in elderly (28). It has also been reported that the percentage of severe RE is higher in the elderly than in juveniles, whereas the frequency of severe heartburn in patients with severe RE is lower in the elderly (27,36).…”
Section: Discussionmentioning
confidence: 91%
“…These clinical characteristics of NERD are also found in western countries; however, more severe gastric atrophy [54,56,84] and the higher rate of H. pylori infection [84] compared with ERD are specific characteristics of Japanese NERD. Joh et al [68] demonstrated that the frequency of abnormal acid reflux with NERD was higher in patients with minimal changes than in patients without such changes. Thus, if gastric acid secretion lead to the development of NERD (grade M or grade N) or ERD, these clinical features found in Japanese NERD could agree with the theoretically advanced features.…”
Section: Advance In the Concept Of Gerdmentioning
confidence: 99%
“…Three studies using the Medical Outcomes Study Short Form-36 (SF-36) demonstrated that HR-QOL in GERD patients was lower than that in the general Japanese population. [66][67][68] A recent study by Hongo et al [69] using a new questionnaire (QOLRAD) which has been developed as a specific QOL assessment of GERD, showed impairment of HR-QOL in GERD patients.…”
Section: Prevalence and Clinical Characteristics Of Symptomatic Gerd mentioning
confidence: 99%
“…Compared to patients with erosive esophagitis, those with minimal change esophagitis were more evenly distributed between males and females, had more gastric atrophy and lacked a hiatal hernia. Others in Japan have found minimal change esophagitis in 49 of 115 patients (43%) with symptoms of heartburn, whereas the remainder had a normal esophagus [7]. It is clear that the concept of minimal change esophagitis has become popular in Japan.…”
Section: New Endoscopic Approachesmentioning
confidence: 99%